Sociodemographic influences on youth sport participation and physical activity among children living within concentrated Hispanic/Latino rural communities - Mary J. Von Seggern; Ann E. Rogers; Michaela A. Schenkelberg; Debra K. Kellstedt; Gregory J. Welk; Robin High; David A. Dzewaltowski (Frontiers Media S.A., 2024)
IntroductionLack of physical activity (PA) among children living in rural communities is a documented public health problem. Although studies have examined community conditions defined by a rural-urban dichotomy, few have investigated rural community conditions with a concentration of Hispanic/Latino people. This cross-sectional study examined sociodemographic characteristics associated with youth sport (YS) participation and daily PA among children living within concentrated Hispanic/Latino rural U.S. Midwest communities.MethodsDuring spring 2022, 97% of 3rd-6th grade children (n = 281, aged approximately 8-12 years) attending school in rural Midwestern communities (n = 2) with >50% concentration of Hispanic students participated in the Wellscapes Project, a community randomized trial. Participants completed the Youth Activity Profile and supplemental National Survey of Children's Health questions assessing PA behaviors and YS participation. Caregivers of a subsample of children (n = 215; males, n = 93; females, n = 122) consented to pair their child's survey results with school enrollment records (e.g., free/reduced lunch status and race and ethnicity). Mixed models with community as a random effect examined main and interaction effects of grade, sex, ethnoracial status, and family income on YS participation and these sociodemographic characteristics and YS participation on daily moderate-to-vigorous PA (MVPA).ResultsApproximately half of children participated in YS. Non-Hispanic White children (n = 82) were over five times more likely to participate in YS than Hispanic peers (n = 133) (OR = 5.54, 95% CI = 2.64-11.61, p < 0.001). YS participants accumulated 8.3 ± 2.3 more minutes of daily MVPA than non-participants (p < 0.001). Sixth graders, females, and Hispanic children reported lower daily MVPA than comparison groups (p < 0.05). Significant interaction effects on daily MVPA between grade and ethnoracial status (F(3, 204) = 3.04, p = 0.030) were also found.DiscussionDisparities in sport participation and PA outcomes based on sociodemographic characteristics exist among children living in ethnoracially diverse rural communities. Strategies to promote YS participation, including community structural changes, may help reduce PA disparities. The research provides valuable insights for policymakers, public health professionals, and community members to address YS participation barriers, not limited to cost, while considering other PA-promotion efforts to improve child population health.